The TESS Triple-9 Catalog: 999 uniformly vetted exoplanet candidates. Issue 1 (15th March 2022) - Cacciapuoti, Luca; Kostov, Veselin B; Kuchner, Marc; Quintana, Elisa V; Colón, Knicole D; Brande, Jonathan; Mullally, Susan E; Chance, Quadry; Christiansen, Jessie L; Ahlers, John P; Di Fraia, Marco Z; Durantini Luca, Hugo A; et al.
ABSTRACT: The Transiting Exoplanet Survey Satellite ( TESS ) has detected thousands of exoplanet candidates since 2018, most of which have yet to be confirmed. A key step in the confirmation process of these candidates is ruling out false positives through vetting. Vetting also eases the burden on follow-up observations, provides input for demographics studies, and facilitates training machine learning algorithms. Here, we present the TESS Triple-9 (TT9) catalog – a uniformly vetted catalog containing dispositions for 999 exoplanet candidates listed on ExoFOP-TESS, known as TESS Objects of Interest (TOIs). The TT9 was produced using the Discovery And Vetting of Exoplanets pipeline, dave, and utilizing the power of citizen science as a part of the Planet Patrol project. More than 70 per cent of the TOIs listed in the TT9 pass our diagnostic tests, and are thus marked as true planet candidates. We flagged 144 candidates as false positives, and identified 146 as potential false positives. At the time of writing, the TT9 catalog contains 20 per cent of the entire ExoFOP-TESS TOIs list, demonstrates the synergy between automated tools and citizen science, and represents the first stage of our efforts to vet all TOIs. Our final dispositions and comments are collected in a supplementary table and the dave -generated files are publicly available on ExoFOP TESS.